Public intellectuals in the global arena : professors or pundits? - Desch, Michael C. (Michael Charles), 1960- (Notre Dame : University of Notre Dame Press, 2016)
What is a public intellectual? Where are they to be found? What accounts for the lament today that public intellectuals are either few in number or, worse, irrelevant? While there is a small literature on the role of public intellectuals, it is organized around various thinkers rather than focusing on different countries or the unique opportunities and challenges inherent in varied disciplines or professions. In Public Intellectuals in the Global Arena, Michael C. Desch has gathered a group of contributors to offer a timely and far-reaching reassessment of the role of public intellectuals in a variety of Western and non-Western settings. The contributors delineate the centrality of historical consciousness, philosophical self-understanding, and ethical imperatives for any intelligentsia who presume to speak the truth to power. The first section provides in-depth studies of the role of public intellectuals in a variety of countries or regions, including the United States, Latin America, China, and the Islamic world. The essays in the second section take up the question of why public intellectuals vary so widely across different disciplines. These chapters chronicle changes in the disciplines of philosophy and economics, changes that "have combined to dethrone the former and elevate the latter as the preeminent homes of public intellectuals in the academy." Also included are chapters that consider the evolving roles of the natural scientist, the former diplomat, and the blogger as public intellectuals. The final section provides concluding perspectives about the duties of public intellectuals in the twenty-first century.
Includes index.
Description based on print version record.
JSTOR
Keywords: Intellectuals; Scholars; Intellectual life; Learning and scholarship; Intellectuels; Savants; Vie intellectuelle; Savoir et érudition.; scholars; Intellectual life; Intellectuals; Learning and scholarship; Scholars; Political; Leadership; BUSINESS & ECONOMICS; Civics & Citizenship; POLITICAL SCIENCE; PHILOSOPHY; Electronic books